Investigation of Passive Filter for LED Lamp - Edi Sarwono; Mochammad Facta; Susatyo Handoko (Proceeding of the Electrical Engineering Computer Science and Informatics, 2016)
Light Emitting Diode lamp or LED lamp is one of the energy saving lamps nowadays widely used by consumers. However, LED lamp has contained harmonics caused by the rectifier circuit inside the lamp. Harmonics cause a quality problem in power system. As the harmonics present in current or voltage, the waveforms are distorted. Harmonics can lead to overheating in magnetic core of electrical equipments. In this paper, several tests are carried out to investigate the harmonic content of voltage and currents, and also the level of light intensity of the two brands of LED lamps. Measurements in this study are conducted by using HIOKI Power Quality Analyzer 3197. The test results show that the total harmonic distortion or THD of voltage on various brands of LED lamps did not exceed 5% as in compliance to the limit of IEEE standard 519-1992. The largest harmonic voltage is 2.9%, while maximum harmonic current for tested brands of LED lamp is 170.6%. The use of low pass filter in the form of LC filter was proposed. Based on experimental results, the application of LC filter at input side of LED lamp has successfully reduced THD current in the range of 85%-88%.